IMPROVING THE EFFICIENCY OF SOLAR PANEL SURFACES BY CLEANING METHODS AND MONITORING THEM - Nimatov Kamoliddin Bakhriddinovich; Nurova Malika Abduzairovna (Scientific Impulse, 2024)
This article covers ways to improve the efficiency of its electrical energy production by cleaning the surface of solar panels from coated dust particles. This includes self-cleaning and solar panel monitoring system, automatic cleaning of solar panels based on microcontroller, electrostatic dust removal, mechanical cleaning methods, electrostatic dust removal methods, from which electrostatic dust removal methods have been analyzed to be more efficient than other methods.